2016
DOI: 10.4103/2229-5178.193906
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis: Epidemiology, clinical features, co-morbidities, and clinical scoring

Abstract: On the basis of current evidence derived from hospital-based studies, mostly from North India, the prevalence of psoriasis in adults varies from 0.44 to 2.8%, with a much lower prevalence in children. The peak age at onset in adults is in the third and fourth decade of life, with a slight male preponderance. It is recommended that population-based large epidemiologic studies should be undertaken in different parts of the country for estimating the correct prevalence of psoriasis in general population. Chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
79
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 55 publications
3
79
0
2
Order By: Relevance
“…At present, the data on the prevalence of psoriasis are from hospital-based studies rather than from well-defined large population-based studies. There is a paucity of data related to genetics, epidemiology, disease types, associations, severity and course amongst Indian patients with psoriasis 3 . Only recently the research on psoriasis from India has started focusing on the genetics and epigenetics of psoriasis and association with metabolic syndrome, and there is a large gap addressing the therapeutic aspects of psoriasis, particularly on the use of biologics.…”
mentioning
confidence: 99%
“…At present, the data on the prevalence of psoriasis are from hospital-based studies rather than from well-defined large population-based studies. There is a paucity of data related to genetics, epidemiology, disease types, associations, severity and course amongst Indian patients with psoriasis 3 . Only recently the research on psoriasis from India has started focusing on the genetics and epigenetics of psoriasis and association with metabolic syndrome, and there is a large gap addressing the therapeutic aspects of psoriasis, particularly on the use of biologics.…”
mentioning
confidence: 99%
“…Psoriasis besides being a skin disorder is also a systemic inflammatory disease leading to atherosclerosis 6 7 . Different cross-sectional and case-control studies across the country have reported higher prevalence of cardiac risk in patients of psoriasis 8 9 .…”
mentioning
confidence: 99%
“…This was similar to the findings in study by Dogra et al and Ayanlowo et al, but in contrast to Raghunandan et al which showed the peak incidence at third and fourth decade of life. 10,16,17 And Ramani et al which showed peak incidence at the age of 35-55 years. 12 The most common type of psoriasis seen in our study was Psoriasis vulgaris otherwise known as plaque type of psoriasis (82.22%) followed by erythrodermic psoriasis (4.44%) and psoriatic arthritis.…”
Section: Discussionmentioning
confidence: 99%